Discriminatory indices of ‘introduction to psychology’ multiple choice examination questions - ODUKOYA, Jonathan Adedayo; OMONIJO, Dare Ojo (Edelweiss Applied Science and Technology, 2024)
This study investigated the discriminatory indices of the multiple choice questions of a compulsory undergraduate course (Introduction to Psychology) in a private Nigerian university. The main research question raised was: Did all the items in the ‘Introduction to Psychology’ examination discriminate adequately between low scoring and high scoring students? To answer this question, the discriminatory index was derived for all the 70 items fielded in the examination. Though 255 students took this course, only students whose total scores fell within the topmost and lowest quartiles participated in this study. Students with missing data were extracted from the topmost and lowest quartiles. Consequently, the data of 100 students (50 in the topmost quartile and 50 in the lowest quartile) were utilized in computing the Discriminatory indices (Di) of the 70 Multiple Choice Questions. Out of the 70 items, two (2.9%) furnished poor Di, fifteen items (21.4%) had weak Di, fourteen items (20%) had fair Di, and thirty-nine items (55.7%) had fairly strong and strong Di. The findings are discussed and relevant recommendations made.